Uluslararası Spor Organizasyonlarının Sosyo-Kültürel Etkileri: 2013 Mersin XVII. Akdeniz Oyunlarına Yönelik Bir Uygulama. - SİLİK, Cemal Ersin; GÜÇER, Evren (Journal of Social Sciences & Humanities Researches)
The purpose of this study is to determine socio-cultural impacts of the international sports organizations on the city where it is held. Therefore, the Mediterranean Games, considered as the most important sporting events after the Olympic Games, was chosen as an example. To achieve the objectives of the research Mega Event Impact Scale developed by Jie and Yan (2010) is used. Socio-cultural statements have been divided into five sub-dimensions by factor analyzing of the statements in the scale. These dimensions are expressed as tourist facilities, international promotion, environmental and cultural preservation, social and environmental problems, cultural change. Perceptions are determined by the local people in Mersin with identified dimensions. Therefore, local people living in Mersin was surveyed in this study. In the target population of the study, sampling size was determined to be ± 0.05 with 384 sampling error and 452 questionnaires have been applied to local residents. In the analysis of the data obtained, "percentage", "frequency", "t-test for independent samples", "singlefactor variance (Anova) analysis", "Tukey (HSD) test" and have been used. According to the results of the survey, the differences in the occupation and income level of the local people with the tourist facilities; gender of the local population with the international promotion; the age of the local people with the environmental and cultural preservation; the income level of the local people with social and environmental problems have been identified. However, it has not found any differences in individual characteristics with the cultural change size.